Word-Formational Creativity in the Literary Opus of the Večernica Prize - Voršič, Ines (Trideset let literarne nagrade večernica, 2026)
The paper focuses on word-formation creativity in selected works of children’s and young adult literature that were either nominated for or awarded the Večernica Prize. The originality and diversity of occasional word formations in the selected texts reveal the playful dynamics of the Slovene word-formation system. Such playfulness proves to be an important and frequent stylistic device in children’s and young adult literature, since witty and imaginative language play is precisely what resonates with young readers, attracts them, and inspires them.